Environmental Management System ISO 14001 factors for promoting the adoption of Cleaner Production practices - De Oliveira, José Augusto; Oliveira, Otávio J. [UNESP]; Ometto, Aldo R.; Ferraudo, Antônio S. [UNESP]; Salgado, Manoel H. [UNESP] (Elsevier, 2016)
The Environmental Management System of ISO 14001 stands out as one of the most widely used systems for managing corporate environmental aspects and processes and the Cleaner Production is a proactive environmental strategy that has remarkably positive results in environmental corporate management. The principal aim of this article was to identify and analyze the influence relations of the ISO 14001 Environmental Management System to the Cleaner Production through a survey-based research. The maturity and the phases of planning and discipline are key factors for the systematization and continuity of Cleaner Production practices. The stages of Planning, Evaluation and Feasibility Study, and Implementation were identified as the main stages of CP fostered by the ISO 14001 Environmental Management System.
Keywords: Cleaner production; Environmental management system; Industrial companies; ISO 14001